The evolution of the adolescent growth spurt: Urinary biomarkers of bone turnover in wild chimpanzees (Pan troglodytes) - Sandel Aaron A; Negrey Jacob D; Arponen Milja; Clark Isabelle R; Clift Jeremy B; Reddy Rachna B; Ivaska Kaisa K (United Kingdom, 2025)
Life history theory addresses how organisms balance development and reproduction. Mammals usually invest considerable energy into growth in infancy, and they do so incrementally less until reaching adult body size, when they shift energy to reproduction. Humans are unusual in having a long adolescence when energy is invested in both reproduction and growth, including rapid skeletal growth around puberty. Although many primates, especially in captivity, experience accelerated growth in mass around puberty, it remains unclear whether this represents skeletal growth. Without data on skeletal growth in nonhuman primates, anthropologists have often assumed the adolescent growth spurt is uniquely human, and hypotheses for its evolution have focused on other uniquely human traits. The lack of data is largely due to methodological difficulties of assessing skeletal growth in wild primates. Here, we use two urinary markers of bone turnover-osteocalcin and collagen-to study skeletal growth in a large, cross-sectional sample of wild chimpanzees (Pan troglodytes) at Ngogo, Kibale National Park, Uganda. For both bone turnover markers, we found a nonlinear effect of age, which was largely driven by males. For male chimpanzees, values for osteocalcin and collagen peaked at age 9.4 years and 10.8 years, respectively, which corresponds to early and middle adolescence. Notably, collagen values increased from 4.5 to 9 years, suggesting faster growth during early adolescence compared to late infancy. Biomarker levels plateaued at 20 years in both sexes, suggesting skeletal growth continues until then. Additional data, notably on females and infants of both sexes, are needed, as are longitudinal samples. However, our cross-sectional analysis suggests an adolescent growth spurt in the skeleton of chimpanzees, especially for males. Biologists should avoid claiming that the adolescent growth spurt is uniquely human, and hypotheses for the patterns of human growth should consider variation in our primate relatives.